The distance seidel spectrum of some graph operations - Deena Scaria; Indulal Gopal (Journal of Hyperstructures, 2024)
The distance matrix, distance eigenvalue, and distance energy of a connected graph have been studied in detail in literature where as the study on distance seidel matrix associated with a connected graph is in progress. The eigenvalues ∂1S≥∂2S≥ ... ≥∂nS of the distance seidel matrix DS(G) of a graph G forms the distance seidel spectrum of G. We describe here the distance seidel spectrum of some types of subdivision related graphs of a regular graph in terms of its adjacency spectrum. We also derive analytic expressions for the distance seidel energy of G(Cp), the partial complement of thesubdivision graph of a cycle Cp and the distance seidel energy of S(Cp), the complement of the even cycle C2p.